HUBUNGAN DUKUNGAN SOSIAL SPIRITUAL DENGAN MOTIVASI SEMBUH KLIEN DI RUANG RAWAT INAP RUMAH SAKIT ST. CAROLUS BORROMEUS KUPANG - Paulina Bau (Universitas Citra Bangsa, 2019)
Spirituality is an essential factor that helps people in achieving the balance needed for nurture health, well-being and to survive the illness. The lack of social and spiritual support will affect patients' healing motivation. Healing motivation is very important for patients as it is one of the factors that will speed up the patient's recovery process. This study aimed to determine the relationship between spiritual-social support and clients' healing motivation in the Inpatient room of Hospital St. Carolus Borromeus Kupang. The research method used was quantitative research and the study design was cross-sectional conducted in the Hospital St. Carolus Borromeus Kupang with a target population of 51 respondents, sampling was conducted by using purposive sampling technique on 47 respondents. Data was collected by relying on the questionnaire sheet. Based on the results of research on the relationship between spiritualsocial support and clients' healing motivation in the Inpatient room of Hospital St. Carolus Borromeus Kupang, it was found that 26 respondents (55.3%) out of 47 respondents had fair social-spiritual support and 21 respondents (44.7%) out of 47 respondents had excellent social-spiritual support. It was also found that 24 respondents (51.1%) out of 47 respondents had fair healing motivation and 23 respondents (48.9%) out of 47 respondents had excellent healing motivation.Spearman rho statistical test results (r2) on the relationship between the level of depression with sleep quality in the elderly obtained p-value of 0.004 that was lower than the value of α (0.05), then Ho was denied and resulted with the fact that there was a relationship between spiritual-social support with client's healing motivation. From the results of this study, it is expected that good social-spiritual support will be maintained in order to increase the client's healing motivation and modify even better spiritual services (spiritual services are daily provided for all religions). Keywords: Social-Spiritual Support, Healing Motivation, Inpatient